Mesoamerican nephropathy - a new challenge for occupational physicians - Katarzyna Kanclerz; Wojciech Wołyniec; Przemysław Rutkowski; Marcin Renke (Nofer Institute of Occupational Medicine, 2020)
Mesoamerican nephropathy (MeN) is an endemic form of chronic kidney disease (CKD) that is not related to risk factors for CKD, such as diabetes and hypertension. It primarily affects men, rural and agricultural laborers, who work in an extremely hot and dry environment. The greatest increase in the prevalence of CKD, particularly since the late 1990s, has been reported in Central America and Southern Mexico, where the prevalence is almost 9 times higher than in the USA. The highest mortality associated with CKD is reported in El Salvador where a 10-fold increase was recorded in 1984-2005. In histological examination, MeN patients manifest tubulointerstitial lesions and, in some cases, also lesions in the glomeruli. The cause of MeN remains unclear. Repeated episodes of occupational heat stress, and sweating accompanied by water loss, have a significant impact on the disease development. The disease is a significant social and economic problem, and a challenge in the field of diagnostics, therapy and prevention for physicians of many specialties, especially for occupational physicians. Med Pr. 2020;71(3):353-61